Applying Mind Mapping Strategy in Fostering Students’ Writing Skill - Mulis (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2022)
This research was conducted to undertake students’ problems in writing skill dealing with the process to produce descriptive text in which there were 28 students of MTs Mambaul Ulum Banjarejo Pagelaran Malang. Regarding to the research design, Classroom Actin Research (CAR) was utilized. The research employed two cycles in which each cycle consisting of two meetings. Dealing with the instruments, test (preliminary and post-test) was applied to obtain data findings. Test covered pre-test and post that was used to investigate students’ prior writing skill score before and after teaching them by using mind mapping. In analyzing students’ writing skill, He utilized writing Scoring Rubric. Finding showed that in preliminary test, students obtaining a minimum mastery criterion (KKM) was 10,71%. It indicated that mostly students’ writing skill was under score minimum. Yet, for the first cycle, students obtaining a minimum mastery criterion was 42,85%. The first cycle showed an improvement of students' writing score. While for the second cycle, students obtaining a minimum mastery criterion was 75,00%. Finding underlined mind mapping was effectively in fostering students’ writing skill. Hence, this research highlighted and recommended mind mapping strategy should be applicated and utilized when teaching writing skill related to descriptive text exactly.